Circularly polarized luminescent systems fabricated by Tröger's base derivatives through two different strategies - Qian, Cheng; Chen, Yuan; Zhao, Qian; Cheng, Ming; Lin, Chen; Jiang, Juli; Wang, Leyong (Beilstein Journal of Organic Chemistry, 2021)
The Tröger's base derivative rac-TBPP was synthesized and separated into two enantiomers R2N-TBPP and S2N-TBPP by chiral column chromatography. These compounds show a strong circularly polarized luminescence with glum values of +0.0021, and −0.0025, respectively. The second way to fabricate the rac-TBPP-based CPL-active material is to co-gel the fluorescent rac-TBPP with a chiral ᴅ-glutamic acid gelator DGG by co-assembly strategy. At the molar ratio of rac-TBPP/DGG = 1:80, the glum value of the co-gel was about three times higher than the glum values of R2N-TBPP and S2N-TBPP enantiomers. Interestingly, the CPL handedness of the rac-TBPP/DGG co-gel could be adjusted effectively by changing their stoichiometric ratios.
Keywords: circularly polarized luminescence; chiral resolution; co-gelation; inversion of CPL handedness; Tröger's base